The Influence of Tool Rotational Speed on Mechanical Properties of Friction Stir Welded Dissimilar AA5083-H112/AA6061-T6 Joints - Andrian Permana; Mochammad Noer Ilman (Universitas Islam Raden Rahmat, Malang, 2024)
The relatively new and innovative welding technique known as friction stir welding (FSW) has found widespread application in the automotive, railway, and aircraft industries. Due to engineering and financial considerations, welding of dissimilar metals is frequently carried out in these industries. During the friction stir welding process, three tool rotational speeds—910, 1500, and 2280 rpm—were utilized, while the welding speed remained constant at 30 mm/min. Several experimental works, including fractography, tensile tests, and observations of the microstructure, were carried out following welding. Results showed that ultimate tensile strength (UTS) and yield strength (YS) expanded as the tool rotational speed was expanded and the best UTS and YS, typically 228 MPa and 156 MPa at the speed of 2280 rpm. The precipitation of AA6061-T6 in the stir zone (SZ) and the increased degree of mixing were linked to the improved weld strengths.